Function of Hrs in endocytic trafficking and signalling. (August 2001) - Raiborg, C.; Bache, K. G.; Mehlum, A.; Stenmark, H.
Abstract : The hepatocyte growth factor-regulated tyrosine kinase substrate, Hrs, becomes tyrosine-phosphorylated upon the binding of various growth factors and cytokines to their receptors. This protein is essential for ventral folding morphogenesis, and it shares structural similarity with Vps27p, which is involved in vacuolar protein sorting in yeast. Since Hrs is localized to endosomes and has been implicated in the regulation of signal transduction as well as membrane trafficking, it has been regarded as a potential co-ordinator of endosomal receptor sorting and signalling. Here we discuss the possible functions of Hrs in light of its interactions with phosphatidylinositol 3-phosphate and multiple proteins.